Better treatment outcomes with aripiprazole long-acting injection in community and incarcerated patients with serious mental illness - Koiliari, Erasmia I.; Mouzas, Ioannis; Alevizopoulos, Georgios; Lesch, Otto; Walter, Henriette; Pasparakis, Emmanouil L. (Frontiers in Psychiatry, 2025)
ImportanceAripiprazole, a partial D2 receptor agonist, is proposed to enhance prefrontal cortex (PFC) dopamine function, improving working memory and GABA transmission, which supports social functioning. Long-acting injectable (LAI) antipsychotics are known to improve patient adherence, leading to enhanced long-term effects on behavioral outcomes.ObjectiveTo evaluate whether aripiprazole LAI treatment improves general functioning, quality of life, and reduces hospitalizations in psychotic patients, both in community settings and within incarcerated populations.Design, settings, and participantsThe study included 55 patients, with 34 from the community and 21 incarcerated at a prison in Southeastern Greece (Neapolis). The World Health Organization Quality of Life Brief Version (WHOQOL-BREF) and the Clinical Global Impression-Severity (CGI-S) scale were used to assess outcomes. Comparisons were made between pre-treatment and post-treatment periods, with a minimum follow-up of six months.Results• Demographics: Community patients (70.6% male) included 44.1% with paranoid schizophrenia. Incarcerated patients (all male) had an F29.0 diagnosis, with 57.1% exhibiting Cluster B personality disorder and all reporting psychoactive substance use.• Hospitalizations: Community patients’ hospitalizations decreased from 1.4 to 0.1 over six months (p=0.001). Incarcerated patients’ hospitalizations dropped from 0.6 to 0.0 (p=0.066), with no significant intergroup difference (p=0.150).• CGI-S: Community patients’ scores improved from 6.0 to 3.9 (p<0.001). Incarcerated patients’ scores improved from 5.3 to 3.2 (p<0.001), with no significant difference between groups (p=0.814).• Quality of Life: Community patients’ scores rose from 0.5 to 3.0 (p<0.001), while incarcerated patients’ scores also increased significantly (p<0.001).ConclusionsThis study of 34 community and 21 incarcerated patients revealed significant demographic and medical history differences. Both groups experienced reduced hospitalizations and improvements in CGI-S scores and quality of life following aripiprazole LAI administration. Community patients showed a greater reduction in hospitalizations, while clinical and quality-of-life improvements were comparable across groups.